Comparison of surface properties and physiological effects of a synthetic and a natural surfactant in preterm rabbits. Issue 3 (November 1994) - Corcoran, J D; Berggren, P; Sun, B; Halliday, H L; Robertson, B; Curstedt, T
Abstract : AIMS–To compare the physical and physiological properties of a synthetic surfactant (Exosurf, Wellcome Foundation) and a natural surfactant (Curosurf, Chiesi Farmaceutici). METHODS–Surface properties of the surfactant suspensions (10 mg phospholipid/ml) were evaluated using the pulsating bubble surfactometer. Lung-thorax compliance was determined in 47 immature newborn rabbits with a gestational age of 27 days, treated with recommended clinical doses of either surfactant (Exosurf 67.5 mg/kg; Curosurf 200 mg/kg). The lungs were examined histologically. RESULTS–The mean (SD) contractile forces of the surface at maximum and minimum bubble size were significantly lower for Curosurf than for Exosurf: 31 (2) and 0 (0) mN/m v 53 (5) and 29 (4) mN/m, respectively. Mean (SD) lung-thorax compliance after one hour of ventilation was significantly higher in rabbits treated with Curosurf compared with animals receiving Exosurf or those serving as controls: 0.60 (0.15) ml/cm H2O.kg v 0.44 (0.03) and 0.34 (0.18) ml/cm H2O.kg, respectively. Both surfactants increased alveolar volume density compared with results for control animals, but only Curosurf significantly reduced the incidence of moderate or severe bronchiolar epithelial disruption. CONCLUSIONS–The natural surfactant, Curosurf, reduced the contractile force at an air-liquid interface to a greater extent than the synthetic surfactant, Exosurf, and led to a greater improvement in compliance and less airway epithelial damage when given in clinical treatment doses to immature rabbits.